Considerations in implementing evidence-based early autism spectrum disorder interventions in community settings - Stahmer, Aubyn C.; Dababnah, Sarah; Rieth, Sarah R. (Pediatric Medicine, 2019)
Evidence-based practices (EBPs) in early intervention for autism spectrum disorder (ASD) have the potential to improve children’s developmental trajectories and address family needs. However, the successful use of EBPs in community early intervention settings requires careful attention to the context in which services are delivered. Implementation science, and specifically the Exploration, Preparation, Implementation, and Sustainment (EPIS) Model, provides a framework to examine context across multiple levels and identify barriers and facilitators to community EBP use. This article identifies several considerations most relevant for early intervention in ASD at the outer and inner context levels, as well as bridging and innovation factors. Outer context considerations include the policies and funding streams surrounding service delivery, the role of advocacy in shaping the service landscape, the availability of appropriate specialists to provide services, and family cultural characteristics. Inner context factors include the individual characteristics of both the children receiving the service as well as the provider delivering the service, in addition to the leadership and organizational climate surrounding the use of a particular EBP. We also discuss considerations of the specific innovation (in this case, EBP early interventions) to be deployed, as well as bridging factors.